answersLogoWhite

0


Best Answer

10t=6t+24

-6 -6

4t=24

4 4

1=6

t=6

User Avatar

Wiki User

โˆ™ 2010-05-28 03:40:41
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: 10t equals 6t plus 24
Write your answer...
Submit
Related questions

What is 3s plus 4t plus 2s plus 5s plus 6t equals?

3s + 4t + 2s + 5s + 6tGroup all of the like 's' terms & 't' terms together:(3s+2s+5s) + (4t + 6t)10s + 10t or 10(s+t)


What is the answer to 8t plus 5 equals 6t plus 1?

t=-2


What is the answer for 8t plus 5 equals 6t plus 1?

8t + 5 = 6t + 1,subtract 6t an 5 from each side,2t = -4t = -2Checking, 8t + 5 = -16 + 5 = -11 and 6t +1 = -12 + 1 = -11


6t plus 7 when t equals -3?

6t + 7 when t = -3 is 6*(-3) + 7 = -18 + 7 = -11


What is 4 t plus 1 equals 6t-1?

t=1


What is 6T plus T?

6t+t = 7t


What is the answer for 3t2 plus 5t plus 6t plus 2t2 - 6t -4?

3t2 + 5t + 6t + 2t2 - 6t - 4is the same thing as 5t2 + 5t - 4.But that's not an 'answer'. There's no question in the original expression.


What is the answer to 6t plus 5?

As an algebraic expression it is simply: 6t+5


What is 6t for t equals 2?

6t 6(2) t=2 12 The answer is 12.


What is 6t-2t plus 5u?

6t -2t + 5u = 4t - 5u


How do you simplify 3t plus 6t?

9t2


Simplify 2r plus 7r - 6t - r plus 7t?

2r + 7r - 6t - r + 7t = 8r + t


How do you solve this equation -4t plus 5t-8 plus 4 equals 6t-4?

-4t+5t-8+4=6t-4 eqn soln t=0 transpose variable terms on one side & constant terms on the other side of equality


Who holds has the most 1 ranking all time in the ap football poll?

Most Associated Press National ChampionshipsSince 1936, the Associated Press has polled sportwriters resulting in an annually awarded national championship. Until 1968, the final poll was conducted before the bowl games were played.1 Notre Dame 8 1988 2 Oklahoma 7 20003 Alabama 6 19924t USC 5 20044t Miami (FL) 5 20014t Ohio State 4 20026t Nebraska 4 19956t Minnesota 4 19609t Texas 3 20059t Michigan 3[5] 199710t LSU 2 200710t Florida 2 200610t Florida State 2 199910t Tennessee 2 199810t Penn State 2 198610t Pittsburgh 2 197610t Army 2 194510t Georgia Tech 2 1990


What is t plus 5t plus 5?

t + 5t + 5 = 6t + 5


6t - t plus 6 simplified?

12


What does t equal in the equation 7t-t equals 54?

-47


Which coordinate point lies on the graph with a equation of D equals 6t 32?

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared", "cubed" etc.There is no symbol between 6t and 32.Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared", "cubed" etc.There is no symbol between 6t and 32.Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared", "cubed" etc.There is no symbol between 6t and 32.Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals", "squared", "cubed" etc.There is no symbol between 6t and 32.


How do you work the problem 15-6t equals 11t?

Form the equation: 15-6t = 11t. Add 6t to both sides of the equation to obtain: 15 = 17t or 17t = 15. Divide both sides of the equation by 17 to obtain: t = 15/17.


How do you factor t2 plus 6t-7?

(t + 7)(t - 1)


What is 6t squared minus 2t squared?

For "6t - (2t2)", it is not reducible. For "(6t - 2t2)", it is 16t2


What is 6t squared plus 17t plus 7?

6t2+17t+7 = (3t+7)(2t+1) when factored


What is the answer to 6t-1 over 69 what does t equal?

(6t - 1) / 69 = 1 6t - 1 = 69 6t = 70 t = 70 / 6


Factor 3tx plus 6t plus 3hx plus 6h?

3tx + 6t + 3hx +6h = 3(tx + 2t +hx +2h) = 3[t(x + 2) + h(x + 2)] = 3(x + 2)(t + h)


What is 6t2-53t plus 40 factored out?

6t2 - 53t + 40 = 6t2 - 48t - 5t + 40 = 6t(t - 8) - 5(t - 8) = (t - 8)(6t - 5)